Validation of a novel very large eddy simulation method for simulation of turbulent separated flow. (15th May 2013) - Han, Xingsi; Krajnović, Siniša
SUMMARY: The paper describes the validation of a newly developed very LES (VLES) method for the simulation of turbulent separated flow. The new VLES method is a unified simulation approach that can change seamlessly from Reynolds‐averaged Navier–Stokes to DNS depending on the numerical resolution. Four complex test cases are selected to validate the performance of the new method, that is, the flow past a square cylinder at Re = 3000 confined in a channel (with a blockage ratio of 20 % ), the turbulent flow over a circular cylinder at Re = 3900 as well as Re = 140, 000, and a turbulent backward‐facing step flow with a thick incoming boundary layer at Re = 40, 000. The simulation results are compared with available experimental, LES, and detached eddy simulation‐type results. The new VLES model performs well overall, and the predictions are satisfactory compared with previous experimental and numerical results. It is observed that the new VLES method is quite efficient for the turbulent flow simulations; that is, good predictions can be obtained using a quite coarse mesh compared with the previous LES method. Discussions of the implementation of the present VLES modeling are also conducted on the basis of the simulations of turbulent channel flow up to high Reynolds number of Re τ = 4000. The efficiency of the present VLES modeling is also observed in the channel flow simulation. From a practical point of view, this new method has considerable potential for more complex turbulent flow simulations at relative high Reynolds numbers. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Detailed validation of a newly developed very LES model is presented for the turbulent separated flows such as the flow past a square cylinder, circular cylinder, and a backward‐facing step at different Reynolds number. The model was found to be able to produce quite satisfactory results on quite coarse mesh compared with conventional LES. The model has considerable potential in the predictions of complex turbulent high‐Reynolds‐number flow in engineering applications.